Cover Image, Volume 12, Issue 6. (20th June 2018) - Greene, Jacqueline J.; McClendon, Mark T.; Stephanopoulos, Nicholas; Álvarez, Zaida; Stupp, Samuel I.; Richter, Claus‐Peter
Abstract : The cover image, by Jacqueline J. Greene et al., is based on the Research Article Electrophysiological assessment of a peptide amphiphile nanofiber nerve graft for facial nerve repair, https://doi.org/10.1002/term.2669